Etika Bisnis Islam: Pondasi Utama Bagi Badan Usaha Milik Ma’arif NU Banyuwangi - Ma’rifatul Munawaroh (Journal of Islamic Economics and Finance, 2023)
This study aims to describe the application of Islamic business ethics as the main foundation for the Ma'arif NU Banyuwangi business entity. The method applied in this study is qualitative research. In this study, data collection techniques used include observation, interviews, and documentation. This study uses interactive analysis for data analysis. The results of this study indicate that the application of Islamic business ethics in the Ma'arif NU Banyuwangi Business Entity is the main foundation for running a fair, sustainable, and ethical business. Principles such as monotheism, balance, responsibility, freedom within the limits of sharia, and Ihsan form the basis for business management, which not only prioritizes material profit but also social and spiritual welfare. With Islamic business ethics, this business entity is able to build public trust and create broad benefits for all parties involved.